Analysis of communication styles underpinning clinical decision-making in cancer multidisciplinary team meetings - Soukup, Tayana; Lamb, Benjamin W.; Green, James S. A.; Sevdalis, Nick; Murtagh, Ged (Frontiers in Psychology, 2023)
Introduction In cancer care, multidisciplinary team (MDT) meetings are the gold standard. While they are trying to maximize productivity on the back of the steadily increasing workload, growing cancer incidence, financial constraints, and staff shortages, concerns have been raised with regards to the quality of team output, as reported by Cancer Research UK in 2017: “Sometimes we discuss up to 70 patients. This is after a whole day of clinics, and we do not finish until after 19.00. Would you want to be number 70?”. This study aimed to explore systematically some of the dynamics of group interaction and teamwork in MDT meetings. Materials and methods This was a prospective observational study conducted across three MDTs/university hospitals in the United Kingdom. We video-recorded 30 weekly meetings where 822 patient cases were reviewed. A cross-section of the recordings was transcribed using the Jefferson notation system and analyzed using frequency counts (quantitative) and some principles of conversation analysis (qualitative). Results We found that, across teams, surgeons were the most frequent initiators and responders of interactional sequences, speaking on average 47% of the time during case discussions. Cancer nurse specialists and coordinators were the least frequent initiators, with the former speaking 4% of the time and the latter speaking 1% of the time. We also found that the meetings had high levels of interactivity, with an initiator–responder ratio of 1:1.63, meaning that for every sequence of interactions initiated, the initiator received more than a single response. Lastly, we found that verbal dysfluencies (laughter, interruptions, and incomplete sentences) were more common in the second half of meetings, where a 45% increase in their frequency was observed. Discussion Our findings highlight the importance of teamwork in planning MDT meetings, particularly with regard to Cancer Research UK in 2017 cognitive load/fatigue and decision-making, the hierarchy of clinical expertise, and the increased integration of patients' psychosocial information into MDT discussion and their perspectives. Utilizing a micro-level methodology, we highlight identifiable patterns of interaction among participants in MDT meetings and how these can be used to inform the optimization of teamwork.